Memórias Flageladas: a construção da seca na região do Cariri cearense (1958 – 1970) - Sousa, Bartolomeu Humberto de (2016)
This work - linked to the line of research Regional History Graduate Program in History at the Federal University of Paraiba, with Concentration Area in History and Historical Culture - aims to discuss and analyze the memories produced on droughts in the Region of Ceará Cariri engendered on oral narratives and written records, highlighting the particularities and peculiarities of the region, mapping and discussing the ruptures and continuities cultural, geographic and historical on traditional historiography. Thus, it is necessary to understand and situate in time and space characteristics of caririense Region in contrast to the state of Ceará and even the Northeast, contextualizing these features since colonization, analyzing the first crops and economic activities, provided by the favorable climate resulting from Araripe. More sharply, our analysis back to the twentieth century, more precisely in the years 1958 and 1970 to analyze the constant mnemonic and representing variations of these droughts that occurred over the region. Thus, it became interesting to understand how is the process of building the memories of the drought, looking meditate on tensions involving oral narratives and written records, analyzing also disputes by these memories.